PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN ASSEMBLR EDU TERHADAP HASIL BELAJAR SISWA KELAS V UPTD SDN LONGKEK 1 - Aida, Nur; Utfa, Lailatul; Hasanah, Alfiatul; Susilowati, Diana; Rohman, Achmad Habibur; Rahmawati, Ika Dian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effect of using Augmented Reality-based learning media, specifically Assemblr Edu, on improving the learning outcomes of fifth-grade students on the topic of the water cycle at UPTD SDN Longkek 1. The background of this research stems from students' low comprehension of the water cycle material, primarily due to the dominance of conventional, non-interactive teaching methods. A quasi-experimental method was employed using a One Group Pretest-Posttest design. The sample was selected through non-probability sampling, specifically saturated sampling, involving a total of 22 students whose learning outcomes were assessed before and after the use of Assemblr Edu. The research instrument consisted of multiple-choice tests, and the data were analyzed using normality testing and a paired sample t-test. The results showed an increase in the students’ average scores from 43.5 (pretest) to 73.6 (posttest). The t-test yielded a significance value of 0.000 < 0.05, indicating a statistically significant difference. Thus, it can be concluded that the use of Assemblr Edu media has a positive impact on improving student learning outcomes in the water cycle topic. This study recommends the integration of technology-based learning media as an innovative strategy to support science education in elementary schools. Keywords: Learning media, Assemblr Edu, learning outcomes, water cycle, science education